Comparação entre limiar anaeróbio determinado por variáveis ventilatórias e pela resposta do lactato sanguíneo em ciclistas - Okano, Alexandre Hideki; Altimari, Leandro Ricardo; Simões, Herbert Gustavo; De Moraes, Antonio Carlos; Nakamura, Fábio Yuzo; Cyrino, Edilson Serpeloni; Burini, Roberto Carlos [UNESP] (FapUNIFESP (SciELO), 2006)
Many investigations have shown that the coincidence between the ventilatory thresholds and those thresholds using the lactate response does not happen all of the time, suggesting that there is no relationship between the cause-effect between these phenomena. Thus, the present study had as main purpose to compare and correlate the Oxygen consumption (V̇O 2), the power (W), and the heart rate (HR) values attained using protocols to determine the Ventilatory Threshold (VT) and the Individual Anaerobic Threshold (IAT). The sampling was constituted by eight State and National level cyclists (age: 27.88 ± 8.77 years; body mass: 65.19 ± 4.40 kg; height: 169.31 ± 5,77 cm). The IAT was determined starting from a three minutes 50 W warm up with progressive increases of 50 W.3min -1 up to achieving the voluntary exhaustion, when the blood was collected in the last 20 seconds of each phase, and during the recovering period. In order to determine the VT, it was used the same protocol used to determine the IAT, but without performing the blood collection. The VT was identified through the changes in the pulmonary ventilation, as well as of the ventilatory equivalent of the O 2 and CO 2. The t-Student test showed no significant statistical difference in any of the attained variables. The associations found were high and significant. The V̇O 2 (ml.kg -1.min. -1), P (W), and HR (bpm) corresponding to the VT and IAT, as well as the associations between variables were respectively: 48.00 ± 3.82 vs. 48.08 ± 3.71 (r = 0.90); 256.25 ± 32.04 vs. 246.88 ± 33.91 (r = 0.84); 173.75 ± 9.18 vs. 171.25 ± 12.02 (r = 0.97). According to the results attained, it can be concluded that the IAT and the VT produce similar V̇O 2, W, and HR values, favoring the adoption of the VT because it is a non-invasive method to determine the anaerobic threshold in cyclists.
Comparison between anaerobic threshold determined by ventilatory variables and blood lactate response in cyclists
Keywords: Anaerobic threshold; Blood lactate response; Cyclists